Examining the basis of isoniazid tolerance in nonreplicating Mycobacterium tuberculosis using transcriptional profiling. (August 2010) - Tudó, Griselda; Laing, Ken; Mitchison, Denis A; Butcher, Philip D; Waddell, Simon J
Background: Understanding how growth state influences Mycobacterium tuberculosis responses to antibiotic exposure provides a window into drug action during patient chemotherapy. In this article, we describe the transcriptional programs mediated by isoniazid (INH) during the transition from log-phase to nonreplicating bacilli, from INH-sensitive to INH-tolerant bacilli respectively, using the Wayne model.Results: INH treatment did not elicit a transcriptional response from nonreplicating bacteria under microarophilic conditions (NRP2), unlike the induction of a robust and well-characterized INH signature in log-phase bacilli.Conclusion: The differential regulation (between drug-free NRP2 and log-phase bacilli) of genes directly implicated in INH resistance could not account for the abrogation of INH killing in nongrowing bacilli. Thus, factors affecting the requirement for mycolic acids and the redox status of bacilli are likely responsible for the reduction in INH efficacy. We speculate on additional mechanisms revealed by transcriptome analysis that might account for INH tolerance.